Liver Transplantation in Sri Lanka - Wijeyaratne, M. (Faculty of Medicine, University of Colombo, 2020)
Although kidney transplantation had become well established liver transplantation had not been even attempted when we stepped into the 21st century. A couple of unsuccessful ...
Keywords: Liver; Transplantation; Sri Lanka